2015
DOI: 10.1111/1750-3841.12879
|View full text |Cite
|
Sign up to set email alerts
|

Apple Aminoacid Profile and Yeast Strains in the Formation of Fusel Alcohols and Esters in Cider Production

Abstract: The amino acid profile in dessert apple must and its effect on the synthesis of fusel alcohols and esters in cider were established by instrumental analysis. The amino acid profile was performed in nine apple musts. Two apple musts with high (>150 mg/L) and low (<75 mg/L) nitrogen content, and four enological yeast strains, were used in cider fermentation. The aspartic acid, asparagine and glutamic acid amino acids were the majority in all the apple juices, representing 57.10% to 81.95%. These three amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 37 publications
2
21
3
Order By: Relevance
“…Phenylalanine was the second most abundant amino acid in most of the juices examined, with Rome having the highest proportion of phenylalanine with 49.2 ± 1.0% of the total amino acids, while Enterprise had the lowest proportion of phenylalanine with 4.8 ± 0.06% of the total amino acids. This finding differs from previous reports of phenylalanine representing only a small proportion of the total amino acids in apples, as low as 0.2–0.4% in dessert apples . Trace amounts of phenylalanine were found in British cider apples , and an average of 1.7–4% of the total amino acids was found in Spanish cider apples .…”
Section: Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…Phenylalanine was the second most abundant amino acid in most of the juices examined, with Rome having the highest proportion of phenylalanine with 49.2 ± 1.0% of the total amino acids, while Enterprise had the lowest proportion of phenylalanine with 4.8 ± 0.06% of the total amino acids. This finding differs from previous reports of phenylalanine representing only a small proportion of the total amino acids in apples, as low as 0.2–0.4% in dessert apples . Trace amounts of phenylalanine were found in British cider apples , and an average of 1.7–4% of the total amino acids was found in Spanish cider apples .…”
Section: Resultscontrasting
confidence: 99%
“…While the proportions of amino acids observed in a juice sample from a given cultivar may be influenced by growing season , crop load , site, rootstock and other factors , our data provide insight as to the extent of variation for each amino acid, and the ranges of relative concentrations of amino acids that could be expected in apple juice. The predominance of asparagine among all other amino acids was consistent with previous studies , although some prior research also reported threonine being the predominant amino acid (53.4%) in Fuji apple juice and aspartic acid being the major amino acid (41.1%) in Brazilian dessert apples .…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations